Pengaruh Williams Flexion Exercise Terhadap Penurunan Nyeri Punggung Bawah Miogenik Pada Pengajian Aisiyah Tanjung Sari Ranting Timur Medan - Novalia Susari Putri; Maryaningsih Maryaningsih; Sulaiman Sulaiman (Jurnal Kesehatan dan Fisioterapi, 2023)
Abstract− Background: Changes in the needs and welfare of human life have caused a shift in the pattern of human life in modern times. The increase in population has resulted in an increase in the work productivity of the population with various types of work activities and the level of complaints of disease symptoms such as complaints of low back pain. Objective: This study aimed to determine the effect of William flexion exercise on reducing myogenic low back pain in women recitation aisyiyah Tanjung sari ranting east medan. Method: This study uses a quasi-experimental method with a one-group pre-test and post-test design with purposive sampling and a sample of 30 people. Data analysis with Wilcoxon test. Result: The results of Wilcoxon test is p-value= 0,000 (p<0,05) which means there is an effect of William flexion exercise to myogenic low back pain in women recitation aisyiyah tanjung sari ranting east medan. Conclusion: There is a significant effect between william flexion exercise to myogenic low back pain in women recitation Aisyiyah Tanjung Sari East Medan.Keywords: William Flexion Exercise, Myogenic Low Back Pain